O pensamento conceitual e a formação de professores de Biologia: a transmissão gênica como objeto do conhecimento - Silva, Elisa Vaz Borges (2020)
This research aimed to discuss the importance of thinking as a concept in the training of Biology teachers from the historical and philosophical study of a biological concept. Here we propose to answer the following question: to what extent can the historical-philosophical understanding of the concept of gene transmission contribute to the formation of Biology teachers conceptual thought? Therefore, we seek to explain how the possible relations between History and Philosophy of Science (HFC) and the conceptual thinking of Biology teachers in training can base this profesional’s methods of thinking and teaching, in a critical perspective.The research method used was historical-dialectical materialism (MHD); therefore, we use as basis the thought of theorists like Enges (1976), Kopnin (1978), Lefebvre (1991), Marx e Engels (2007), Marx (2008) and Kosik (2011). We are also based on the Historical- Cultural Theory (VYGOTSKY, 2009) and the theory of Developmental Teaching (DAVYDOV, 1988). It is a theoretical research, of bibliographic character, in which three complementary literature reviews were made, in order to fully understand the object of investigation. n the reviews, we privileged the following themes: the role of HFC and teacher training in the academic research analyzed, the conceptual thinking formation and the Biology knowledge. The initial review consisted of 33 papers (dissertations and theses). In the analysis, we identified that 45% of the works are based on elements of formal logic regarding the conceptions of teacher training, especially by practicalism as a training purpose. The HFC works, for its part, prioritize it as a methodology in itself or content in itself. As a result of this research, we present the historical and philosophical movement for the concept of gene transmission development, articulating the perspective of each philosophical current in Biology (vitalism, physicalism and organicism) in this process, in order to explain the intense relationship between social and natural history. In addition, we seek to advance the relationship between HFC and didactic-pedagogical mediation through the proposal of conceptual thinking formation by the Biology teacher as formative intentionality in teaching. We present, throughout the discussions, elements and conditions necessary for the Biology teacher’s conceptual thinking formation to be recognized and used effectively as a transformative educational praxis.